Narrow vertical divergence 780 nm lasers with modulated refractive index of photonic crystal structure. (1st April 2022) - Xu, Chuanwang; Qi, Aiyi; Wang, Tiancai; Zhou, Xuyan; Qu, Hongwei; Wang, Liang; Wang, Juwen; Wang, Yufei; Zheng, Wanhua
Abstract: Narrow vertical divergence lasers for the 780 nm wavelength based on step index photonic crystal (STIN PC) and graded index photonic crystal (GRIN PC) structure are investigated. The effects of GaAsP and InGaAlAs as quantum well materials on device performance are studied. The STIN PC structure realizes a low threshold current of 0.52 A and high output power of 4.75 W at 5 A, while the GRIN PC structure has lower resistance and vertical divergence angle of only 21°. The device performance of GaAsP as a quantum well material is overall better than that of InGaAlAs.